Gender and contemporary horror in film - Holland, Samantha; Shail, Robert; Gerrard, Steven (Bingley, U.K. : Emerald Publishing Limited, 2019)
The horror genre will always remain current because it reflects our anxieties, shining a light onto our worst fears whilst creating worlds defined by darkness. Horror as a genre has always engaged with era-specific societal mores and moral panics, often about isolation or abandonment, changing family values and the role of women. It is often specifically about how gender is constructed in everyday life. Women are commonly defined in horror by their passivity, or monstrosity/sexuality or victimhood - or a mix of the three. At the same time women in horror are forced into psychological and physical torture ending in violent showdowns in which they emerge damaged but triumphant.Bringing together research from a wide range of established and emerging scholars this edited collection provides an insight into how modern horror films portray femininities, sexualities, masculinities, ageing, and other current issues, exploring the use of vampires, zombies, werewolves and ghosts in films made internationally. This volume, one of three by the same editorial team examining the horror genre, focuses on gender and contemporary horror in film, asking questions about how and if representations of gender in horror have changed. In these readings and re-readings, the authors examine developments in films about vampires, zombies, werewolves and ghosts, in films made internationally.
Prelims -- Introduction -- Bodies -- Boundaries -- Captivity -- Index.
Includes index.
Print version record
Keywords: Horror films -- History and criticism; Sex role in motion pictures; Social Science -- Gender Studies; TV & society